Influence of Personal and Social Factors on Vocational Certainty - Velarde Hernández , Delisahé (Consorcio de Universidades Mexicanas A.C., 2014)
The aim of this study was to identify the influence of the social factors and need of career factors on vocational certainty. The sample included 392 students coursing the third semester of different careers of public and private universities in Hermosillo, Sonora, Mexico. The instrument used was the Comprehensive Scale of Career Factors (IAFC) of Aguilar et al. (1992) version for college students, and included indicators of vocational situation; and, school and social-demographic details. Descriptive analyses were conducted and a structural model was specified and tested. This model explained 23% of the variance of vocational certainty, the model presents practical goodness of fit. In addition, an analysis was conducted of the programmatic content taught in the class of Educational Orientation within the subsystem state baccalaureate, specifically those related to the vocational area; from the model of Posner (2005) and of the taxonomy of types of learning skills of Castañeda, López, García y González (2006). Results suggest the design of educational orientation through development of interventions on the socio-labour, academic and personal areas, with the purpose to ease the academic and professional student elections.